Perbandingan Sistem Kepegawaian Aparatur Sipil Negara Jepang dan Indonesia - Novi Alviani; Savira Fajar Meyriyanih; Sulistia Sulistia; Widodo Widodo; Wijoyo Hartono; Siti Khopipah; Irvan Arif Kurniawan (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Comparing the civil service system is a topic of discussion in comparative public administration. This article compares the civil service systems in Japan and Indonesia in order to draw some useful conclusions for the latter. The Indonesian civil service's total staff, independent institution in charge of the civil system, merit-based hiring, performance-based promotions, and salary structure based on workload, responsibility, and work complexity are all beneficial lessons. Workplace culture is a means of constructing good governance, specifically, a solid and responsible development management that adheres to democratic principles. Efficient market, avoidance of erroneous investment fund allocation, good political and administrative practices in the fight against corruption, implementation of budgetary restraint, and development of a legal and a political framework for expanding the scope of work.